ANCHOR: A Technical Approach to Monitor Single-Copy Locus Localization in Planta - Meschichi, Anis; Ingouff, Mathieu; Picart, Claire; Mirouze, Marie; Desset, Sophie; Gallardo, Franck; Bystricky, Kerstin; Picault, Nathalie; Rosa, Stefanie; Pontvianne, Frédéric (Frontiers in Plant Science, 2021)
Together with local chromatin structure, gene accessibility and the presence of transcription factors, gene positioning is implicated in gene expression regulation. Although the basic mechanisms are expected to be conserved in eukaryotes, little is known about the role of gene positioning in plant cells, mainly due to the lack of a highly resolutive approach. In this manuscript, we adapted the use of the ANCHOR system to perform real-time single-locus detection in planta. ANCHOR is a DNA-labelling tool derived from the chromosome parti-tioning system presents in many bacterial species. We demonstrate its suitability to monitor a single-locus in planta and used this approach to track chromatin mobility during cell dif-ferentiation in Arabidopsis thaliana root epidermal cells. Finally, we discuss the potential of this approach to investigate the role of gene positioning during transcription and DNA repair in plants.